Bacterial profile and antimicrobial susceptibility pattern of community and hospital-acquired urinary tract infections among UTI suspected geriatrics in Gondar town, Northwest Ethiopia - Getachew Bitew Alebachew; Mulat Dagnew; Aklilu Ambachew; Belay Tessema (PLoS ONE, 2025)
Background Bacterial urinary tract infection (UTI) is the second most frequent infection next to respiratory tract infection within the geriatric population both in the community and hospital settings. There is a limited data regarding geriatrics UTI in this study area. Therefore, the current study aimed to assess the status of the community and hospital-acquired urinary tract infections, and antimicrobial susceptibility patterns among UTI suspected geriatrics which is essential to physicians and health care workers to implement appropriate intervention. Methods A comparative cross-sectional study was conducted among 460 UTI suspected geriatrics admitted at the University of Gondar Comprehensive Specialized Hospital and attended in Gondar town (Kallen Bnakafl and Menna Geriatrics Support Center Clinics) from 1st May 2022–14th July 2022. Socio-demographic data were collected using structured questionnaires. Urine culture was performed and isolates were counted for significant growth by a colony counter, and their antibiotic susceptibility was done by the Kirby–Bauer disc diffusion method. Data were entered using Epi Data version 4.0.0 and analyzed by Stata/IC version 14.0. P-value < 0.05 at 95% CI was considered statistically significant. Result The overall prevalence of UTI in geriatrics was 44.4%. The prevalence of UTI among community and hospitalized suspected patients was 38.7% and 50%, respectively. Escherichia coli (E. coli) (38.6%) predominated across the two groups, followed by Klebsiella spp. (15.8%), S. saprophyticus (12.2%), P. mirabilis (9.1%), S. aureus (5.9%), and Citrobacter spp. (2.8%). Pseudomonas spp. (7.1%), K. rhinoscleromatis (5.1%), and P. vulgaris (2.8%), were isolated from only hospitalized patients. Piperacillin-tazobactam susceptibly was 100% in both study groups. Nalidixic acid resistance was 50% to 87.5% and 50% to 100% in the isolates from community and hospitalized UTI suspects, respectively. Conclusion This study found a high prevalence of bacterial UTI in geriatrics and a high rate of bacterial resistance was observed to most antimicrobial drugs tested. Piperacillin-tazobactam and meropenem were the most active antimicrobials for UTI. Therefore, expanding routine bacterial culture and antimicrobial susceptibility testing and strengthening regular surveillance systems are essential for appropriate patient care.